2012
DOI: 10.5829/idosi.ijee.2012.03.03.0924
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Optimization of Energy Consumption in Dairy Farm: Energy Efficiency

Abstract: Abstract:Energy is considered as an important production factor in many systems and therefore should be managed in parallel with other main production resources including land, labor and capital. In this paper, the energy efficiency scores of some selected dairy farms, using the non-parametric data envelopment analysis approach was assessed. The results for efficient farmers based on two DEA models showed that with an energy conservation policy, farmers can perform better in stock farming. The total energy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The yearly requirements of embodied energy in machinery accounted for 3080 MJ per head, a value that underlines the high level of mechanization of the investigated farms. A study conducted by Sefeedpari (2012) [19] on Iranian dairy farms reported about 1641 MJ per cow as the total energy inputs related to machinery. The indirect energy incorporated in the farm machinery and equipment reported as MJ per cultivated land indicates a yearly request of 9270 MJ per hectare, which is in the range of other studies.…”
Section: Farm's Indirect Energymentioning
confidence: 99%
See 1 more Smart Citation
“…The yearly requirements of embodied energy in machinery accounted for 3080 MJ per head, a value that underlines the high level of mechanization of the investigated farms. A study conducted by Sefeedpari (2012) [19] on Iranian dairy farms reported about 1641 MJ per cow as the total energy inputs related to machinery. The indirect energy incorporated in the farm machinery and equipment reported as MJ per cultivated land indicates a yearly request of 9270 MJ per hectare, which is in the range of other studies.…”
Section: Farm's Indirect Energymentioning
confidence: 99%
“…Energy represents an important production factor in agricultural systems and thus should be managed along with the other main production resources [19]. A study carried out by Roer et al (2013) [20], with the aim to assess the environmental impact of combined milk and meat production, shows that excluding the production of building, machinery and materials reduced the Global Warning Potential (GWP) impact approximately by 8% per kg of carcass and 9% per kg of milk.…”
Section: Introductionmentioning
confidence: 99%
“… The total optimum energy requirement for mushroom production was calculated to be 120. 15 As a result of this study, effectiveness of use of all inputs can be achieved in an informed and efficient production system. In this regard, extension programs to-ward the development of such systems should be taken into consideration.…”
Section: Discussionmentioning
confidence: 87%
“…In fact, the input-oriented is commonly utilized in DEA applications because efficiency profitability depends on the efficiency of operations. Besides that, a farmer is able to take the control of inputs use more easily than output level [15,34]. Let the DMU j to be evaluated on any trial be designated as DMU o (o =1, 2, •••, n).…”
Section: Data Envelopment Analysis Techniquementioning
confidence: 99%
See 1 more Smart Citation